A Randomized Controlled Study Comparing Reverse Hybrid Therapy and Standard Triple Therapy for Helicobacter pylori Infection. Issue 48 (December 2015) - Hsu, Ping-I; Kao, Sung-Shuo; Wu, Deng-Chyang; Chen, Wen-Chi; Peng, Nan-Jing; Yu, Hsien-Chung; Wang, Huay-Min; Lai, Kwok-Hung; Cheng, Jin-Shiung; Chen, Angela; Chuah, Seng-Kee; Tsay, Feng-Woei
Abstract : Abstract: Reverse hybrid therapy is an 1-step 2-phase treatment for Helicobacter pylori ( H. pylori ) infection with less cost than standard triple therapy. We conducted a randomized, controlled study to compare the efficacies of standard triple therapy and reverse hybrid therapy in the treatment of H. pylori infection. From October 2012 to March 2015, consecutive H. pylori -infected subjects were randomly allocated to receive either a reverse hybrid therapy (pantoprazole plus amoxicillin for 12 days and clarithromycin plus metronidazole for the initial 7 days) or a standard triple therapy (pantoprazole plus amoxicillin and clarithromycin for 12 days). H. pylori status was assessed 6 weeks after treatment. Additionally, antibiotic resistances and host CYP2C19 genotypes were examined and analyzed. A total of 440 H. pylori -infected patients were randomly assigned to receive either a reverse hybrid (n = 220) or a standard triple therapy (n = 220). The reverse hybrid group had a higher eradication rate than standard triple group either by intention-to-treat (93.6% vs. 86.8%; P  = 0.016) or per-protocol analysis (95.7% vs. 88.3%; P  = 0.005). The 2 patient groups exhibited similar frequencies of overall adverse events (14.1% vs. 9.5%) and drug compliance (96.8% vs. 98.6%). Clarithromycin resistance was an independent risk factor predicting eradication failure in standard triple group ( P  < 0.001), but not in reverse hybrid group. CYP2C19 genotypes did not affect the eradication rates in both groups. Reverse hybrid therapy can be considered for first-line treatment of H. pylori infection since the new therapy achieves a higher eradication rate than standard triple therapy with similar tolerability and less pharmaceutical cost.